A Comparison of Players’ and Coaches’ Perceptions of the Coach-Created Motivational Climate within Youth Soccer Teams - Møllerløkken, Nina Elise; Lorås, Håvard; Pedersen, Arve Vorland (Frontiers in Psychology, 2017)
The coach-created motivational climate within youth sport teams has been shown to be of great importance for the quality of youths' sport experience as well as their motivation for continuing or discontinuing sport participation. While the player perspective on motivational climates has been studied extensively, the coach’s perspective has received considerably less attention, thus little is known about the concordance of perceptions of the motivational climate between coaches and their players, or lack thereof. The purpose of the present study was to directly compare players' and coaches' perceptions of the motivational climate within their respective teams. To this end, 256 male and female soccer players (15-17 years) from 17 different teams and their coaches (n = 29) responded to the Perceived Motivational Climate in Sports Questionnaire (PMCSQ-II). The study design included responses from both coaches and players to the same questionnaire, and both groups were aware of the other part’s participation. Statistical analysis revealed significant differences between players' and coaches' perceptions of the motivational climate. Specifically, players of both sexes perceived the motivational climate to be significantly more performance-oriented and significantly less mastery-oriented compared with the coaches. These findings may advance our understanding of the coach-athlete relationship, and may be of importance for understanding players’ motivation for persistence or discontinuation of the sport.